Pengaruh Harga, Promosi, dan Kualitas Pelayanan terhadap Keputusan Pembelian Tiket Kereta Api Jarak Jauh Nonsubsidi: Studi pada Konsumen Layanan Kereta Api di Universitas Muhammadiyah Surakarta - Ramadhan, Muhammad Farid; Irawati, Zulfa (Masyarakat Ekonomi Syariah Bogor, 2024)
The purpose of this study is to ascertain whether price, promotion, and service quality have an impact on students at Muhammadiyah University in Surakarta's purchase decision to buy non-subsidized long-distance train tickets. Survey research is the method utilized in this study, which employs quantitative research. A questionnaire will be used to get information from respondents. The sampling technique used is a non-probability sampling technique. This research used a sample of 129 respondents. The data processing used in this research uses multiple linear regression analysis, t test, and F test which is processed using the SPSS version 26 application. The results of the t-test in this study showed that while promotion and service quality variables had a positive and substantial impact on purchasing decisions, price variables had no visible effect on those decisions. The study's F test findings show that the combination of price, promotion, and service quality significantly influences consumers' decision to buy.